PKM Legal Assistance In Efforts To Inventory Traditional Cultural Expressions In The Traditional Village Of Pangkung Karung Gede, Pangkung Karung Village, Kerambitan Sub-District, Tabanan District, Bali Province - Diah Gayatri Sudibya; I Wayan Werasmana Sancaya; Kade Richa Mulyawati (Community Service Journal of Law, 2024)
In community service for the 2024 academic year, we from the PKM UNWAR Team provided assistance to the community and traditional artists in Pangkung Karung Gede Village, Kerambitan District, Tabanan Regency, in terms of obtaining intellectual works in the form of art and culture owned by communal communities or also known as Traditional Cultural Expressions. One of the Traditional Cultural Expressions is the Sanghyang Memedi Dance of Pangkung Karung Gede Traditional Village, Tabanan Regency. Over time the dance began to be forgotten because it was included in the category of sacred dance in Balinese customs and culture, so it could only be danced at certain times. In this community service, where the community wants legal assistance in recording Copyright for Sanghyang Memedi Dance in Pangkung Karung Gede Traditional Village, Tabanan Regency has not been implemented, this is due to the lack of legal understanding of the community and cultural factors of the community who still consider recording to be of little benefit. We from the PKM UNWAR Team, in carrying out this community service, found that the problem is that the knowledge and ability of human resources in an effort to inventory traditional cultural expressions in the Pangkung Karung Gede Traditional Village is not optimal. Based on the above problems, we, from PKM UNWAR, are determined to provide assistance to the parties in making a cooperation agreement to avoid unwanted things in the future, so that cooperation can be carried out properly.